A NOVEL FINGERPRINT POWDER FORMULATION BASED ON NIAGRA BLUE DYE: A PRELIMINARY EVALUATION (Journal of Forensic Medicine & Toxicology, 2020)
Fingerprints are the most infallible means of identification. It is important physical evidence usually found on various items recovered from the crime scenes. It can be used to ascertain the identity of person and provide a direct link to the suspect. Wide range of methods (optical, physical and chemical) can be used detect latent fingermarks on porous and non-porous items recovered from crime scenes. A novel fingerprint powder composition based on Niagara blue has been formulated and used for developing latent fingermarks. The formulation develops sharp and clear fingerprints on wide range of dry, smooth, non-porous surfaces such as glass, aluminum foil, metallic spoon, wooden table etc. which may be discerned in natural light. This formulation is useful in detecting and developing weak and fragmented chance prints from scene of crime. The developed formulation is non-hazardous, non-toxic and cost-effective in nature.
Keywords: Fingerprints; Latent impressions; Powder method; Niagara blue; Non-porous surfaces